PERLINDUNGAN RITEL LOKAL DAN PEMBERDAYAAN PASAR TRADISIONAL SEBAGAI USAHA PENINGKATAN EKONOMI LOKAL DI KABUPATEN TANAH DATAR TAHUN 2020 - fatimah amalia putri; Muhammad - Adnan (Journal of Politic and Government Studies, 2021)
This research is about the government's efforts in protecting traditional local retail and empowering traditional markets to improve the economy of local communities. In this study, the authors use the legal basis of West Sumatra Provincial Regulation Number 3 of 2016 concerning Development and Empowerment of People's Markets as a form of successful or not implementation of government policies. The purpose of this study focuses on empowering traditional markets in Tanah Datar Regency and protecting local retailers to improve the regional economy. Using qualitative-descriptive research methods with in-depth interviews. From the results of the study, it was found that an attempt was made to prevent the entry of networked modern retailers into West Sumatra as a basis for local retail protection as well as a basis for local governments to empower traditional markets. The implementation of traditional market empowerment and fostering policies based on West Sumatra provincial regulation number 3 of 2016 runs quite well even though there are deficiencies in the communication process. The empowerment and protection provided to the government has succeeded in improving the regional economy from year to year.